(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines how the elements of water, sky, and earth are metaphorically employed in English and Uzbek idioms and proverbs. Using a cross-cultural semantic approach, it demonstrates the role of metaphor in expressing ecological awareness, emotional states, and moral teachings within each language community. By identifying shared conceptual metaphors and culturally unique variations, the study uncovers the deep-seated influence of environment, tradition, and worldview on metaphorical language.